Analisis Pengaruh Rasio Camel terhadap Kondisi Financial Distress Bank Umum di Indonesia - Sisca Sisca; Mochamad Nugraha Reza Pradana (EkoPreneur, 2020)
This study aims to determine and analyze predictions of financial distress conditions in commercial banks in Indonesia by testing the effect of the CAMEL ratio. The population used in this study is a company registered with the Financial Services Authority (OJK)in the period 2013 to 2017. The independent variables used in this study are the Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Operational Costs on Operating Income (BOPO), Return On Assets (ROA) and Loan to Deposit Ratio (LDR). The number of research data samples consisted of 96 banks in Indonesia which included commercial banks, non-foreign banks, regional development banks and also foreign banks or as many as 480 observation data with data collection methods in the form of purposive sampling. Research data is obtained from bank financial reports published at BI and OJK through the websites www.bi.go.id and www.ojk.go.id. The data obtained will be tested using the binary logistic regression method. The test results proved that the ratio of NPL, ROA and LDR has a significant effect on the condition of financial distress, while CAR and BOPO do not have a significant effect on financial distress conditionsKeywords: CAMEL ratio; financial distress; commercial banks